FINANCIAL RISK MANAGEMENT SYSTEM (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Through the rapid development of the insurance market in Uzbekistan, by the end of 2022, respectively, compared to 2018, the share of insurance services in the gross domestic product (GDP) will be 2.0; the volume of total insurance premiums is 3.3; total assets of insurance organizations 2.1; to increase the number of types of insurance services by 1.7 times” determination requires the strengthening of the role of the insurance market and the wide use of insurance tools. Accordingly, during the comprehensive classification of the content of the